Implementation Of Computer Programming Mathematical Algorithm On A Server With The Debian Linux Operating System Via Virtualbox As Supporting The Admission Of New Students In Vocational Schools - Sina, Ibnu; Santoso, Nugroho Adhi; Ahmadi (Integral (Jurnal Penelitian Pendidikan Matematika), 2024)
In a network connected to the internet, a server computer or computer program is needed that can act as another computer to make requests for content from the internet or intranet. Apart from that, the server computer acts as a gateway to the internet world for each client. Thus, local networks that are connected to other networks or the internet are not directly connected to external networks or the internet, but must pass through a gateway, which acts as a boundary between the local network and the external network. The internet connection is shared among all computers through a component that functions as a proxy server. As is known, algorithm is a syllable that originally originated from mathematics and programming which originated from a computer or cellular network. Therefore, its use can be linked to one of the roles in the operating system where there is a programming algorithm. The purpose of this research is for researchers to carry out the process of learning about work methods and activities in an agency in the field directly. Researchers can get to know the actual work atmosphere so that they can build a good work ethic as well as an effort to broaden their work horizons, and increase their insight and knowledge of information technology in general. general, and especially in server implementations with programming algorithms. Mikrotik in this research is an operating system used to turn a computer into a reliable network router, including various features created for IP networks and wireless networks, suitable for use by Internet Service Providers (ISP) and hostspot providers. In this research, the proxy was installed built in to the router. Bina Islam Mandiri Kersana Vocational School is also one of the Vocational High Schools leading to the National Standard School. Therefore, human resources are also expected to support this goal. To obtain superior human resources, the new student admissions system has begun to set appropriate criteria and is also prepared as fully as possible.